HUBUNGAN PERTUMBUHAN EKONOMI INDUSTRI DENGAN KUALITAS LINGKUNGAN DI KABUPATEN BANJAR, KALIMANTAN SELATAN - Naufal Fikri; Rosalina Kumalati; Ellyn Normelani (Pelantar Press, 2024)
Economic growth in a region is generally driven by increased industrial activity, but this is often accompanied by pressure on environmental quality. This study aims to analyse the relationship between industrial economic growth and environmental quality in Banjar Regency, South Kalimantan. The method used is a descriptive quantitative approach using secondary data in the form of Gross Regional Domestic Product (GRDP) for the industrial sector and environmental indicators (water quality, air quality, and land cover) from relevant institutions for the period 2015–2024. The results of the analysis show that the contribution of the industrial sector to GRDP increased by an average of 4.3% per year, in line with the increase in the number of manufacturing industries in the study area. This increase was accompanied by a decline in the water quality of the Martapura River, high particulate emissions in industrial areas, and reduced land cover due to conversion. Nevertheless, environmental control policies through the implementation of Environmental Impact Assessment (EIA), waste monitoring, and the promotion of green industry began to play a role in slowing the rate of environmental degradation. These findings support the Environmental Kuznets Curve (EKC) hypothesis, which explains that environmental degradation occurs in the early stages of industrialisation, but in the subsequent phase, environmental quality can be restored as awareness increases and sustainable policies are implemented. Thus, it can be concluded that there is a positive relationship between industrial growth and environmental degradation in Banjar Regency, although this can still be controlled through sustainable development strategies.